2013
DOI: 10.4236/ijcm.2013.412a1003
|View full text |Cite
|
Sign up to set email alerts
|

The JAK2<sup>V617F</sup> Mutation Seen in Myeloproliferative Neoplasms (MPNs) Occurs in Patients with Inflammatory Bowel Disease: Implications of a Pilot Study

Abstract: Patients with IBD frequently have hematologic abnormalities suggestive of JAK2 mutated MPNs, but are traditionally classified as reactive processes. Haplotype 46/1 is a well-characterized genetic predisposition, common to both inflammatory bowel disease (IBD) and myeloproliferative neoplasms (MPN). In view of this shared genetic predisposition, we measured the frequency of the JAK2 V617F mutation in IBD patients with thrombocytosis or erythrocytosis, in order to ascertain whether a higher than expected proport… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 25 publications
0
12
0
Order By: Relevance
“…Autoimmune disease, most notably inflammatory bowel disease, has been associated with an increased risk of clonal hematopoiesis. Analysis of patients with thrombocytosis in an inflammatory bowel clinic revealed that 23% of them harbored JAK2 V617F mutations [30], this highlights that some cases of assumed reactive thrombocytosis in a patient with an inflammatory disease may actually be MPN. Also, a cohort of patients with ulcerative colitis was found to have an increased rate of CHIP, in particular with DNMT3A and PPM1D mutations [17].…”
Section: Infections and Auto-immune Disordersmentioning
confidence: 88%
“…Autoimmune disease, most notably inflammatory bowel disease, has been associated with an increased risk of clonal hematopoiesis. Analysis of patients with thrombocytosis in an inflammatory bowel clinic revealed that 23% of them harbored JAK2 V617F mutations [30], this highlights that some cases of assumed reactive thrombocytosis in a patient with an inflammatory disease may actually be MPN. Also, a cohort of patients with ulcerative colitis was found to have an increased rate of CHIP, in particular with DNMT3A and PPM1D mutations [17].…”
Section: Infections and Auto-immune Disordersmentioning
confidence: 88%
“…However, the results are inconclusive, and recently published data again show diverging results of the risk for hematological malignancies in patients with IBD [13,14]. Of note, the specific relationship with MPNs has been sparsely investigated in patients with IBD, since MPNs have not been included as myeloid malignancies in all previous studies [12,14,15]. Nevertheless, Cheddani and colleagues found that the risk of myeloid malignancies (chronic myeloid leukemia, acute myeloid leukemia, ET, PV, and MF), was increased 2-fold among 844 elderly patients with IBD from France compared to that observed in a population-based cancer registry [14].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, as the specific JAK2 rs10758669 single nucleotide polymorphism, part of the haplotype 46/1, is shown to be associated with both CD and UC [ 27 , 28 , 30 ]. Strengthening the notion of shared genetic predisposition, Kuriakose and colleagues showed that the JAK2 V617F mutation was present in four of 23 patients with IBD who also had increased erythrocyte or platelet counts [ 15 ]. Further, in patients with MPN, a correlation between JAK2 V617F positivity and prior autoimmune disease has been observed [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been proposed that the JAK2 46/1 haplotype results in an augmented response to cytokine stimulation, leading to increased inflammation [ 21 ]. Interestingly, a study found JAK2 V617F in about 20% of people with mild thrombocytosis in an inflammatory bowel disease (IBD) clinic, suggesting that a significant fraction of people with IBD harbor a JAK2 V617F clone [ 22 ]. In addition, MPN patients have a >2-fold increased risk of IBD, a result that links these two disease entities with potentially common predispositions.…”
Section: Inflammation Is a Clinical Concern For Myeloid Malignancimentioning
confidence: 99%